PENGETAHUAN ECOLABEL DI INDONESIA VERSUS PENGETAHUAN ECOLABEL DI NEGARA MAJU YANG BERPENGARUH PADA NIAT DAN KEPUTUSAN PEMBELIAN - Bobby Oktavian Susilo (Universitas Trunojoyo Madura, 2016)
The deterioration of our environment has increased people’s environmental awareness these days. This awareness act can be done through the procurement of certified products as ecolabeling and provides knowledge on ecolabeling. Each country has their own individual preferences in ecolabeling policy. Also, consumers in Indonesia and in other developed countries have different knowledge about it. Thus, creating differences in purchase intentions and purchasing decisions on ecolabelled products. In Indonesia, the knowledge of ecolabel is still low while it is high in other developed countries. The effect of low knowledge about ecolabeling is a lack of awareness of environmental damage and the level of purchase intention and purchase intention and decisions. Government plays an active role in the public’s knowledge about ecolabelling.